The Efficiency of Human Resources Management Sharia Hotel in Riau Province - Saib, Khaidir; Mardan, Jhonny Ardan; Anuar, Saiful (ADPEBI, 2022)
At this time technological developments have a major influence on the development of tourism. This development was also followed by the development of hotel business in Riau Indonesia. Almost all cities are built by hotels, both big cities and small cities build one-star hotels to five-star hotels. The hotel business provides a fairly high profit, so that it can affect the income of the state and the surrounding community. But unfortunately, in order to increase hotel revenue, some hotels ignore the conditions for hotel visitors. Many hotels allow unmarried couples to spend the night. It is not surprising that many people say that hotels are places for immorality, gambling, liquor and drugs. In this case, providing opportunities for hoteliers to build hotels based on sharia. Methodology This research uses qualitative methods. Qualitative research is research that is used to study the state of natural objects, where the researcher is the main instrument. The purpose of qualitative research is to describe a phenomenon as deeply as possible by collecting the deepest data, which shows the importance of depth and detail of the data studied. Conclusion of this research is that 1. The employee recruitment process at the Riau sharia hotel chooses to use a closed method by prioritizing moral values (attitudes) and employee honesty. 2. Sharia hotel human resources in Riau Province have efficiency to improve employee performance. 3. that sharia hotels in Riau Province have the ability to improve employee discipline. 4. that the Syariah Hotel in Riau has conducted education and training. Training and development programs are one of the important activities that organizations invest in human resources